2013
DOI: 10.1002/ps.3501
|View full text |Cite
|
Sign up to set email alerts
|

A novel Cph-like gene involved in histogenesis and maintenance of midgut in Bombyx mori

Abstract: The Cph-like gene is a midgut-specific novel gene in B. mori that may participate in histogenesis and midgut maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…When 20E or DMSO was co-cultured with Escherichia coli or Bacillus subtilis , neither significantly inhibited bacterial growth (data not shown). The microflora in feeding larval midguts of silkworms have been studied extensively, and several genera of bacteria were identified that were primarily Micrococcus , Bacillus and Corynebacterium [46, 47]. In the midguts of molting larvae in this study, the cultivatable bacteria were mainly Escherichia coli and Staphylococcus aureus, even though the number was very low (data not shown).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…When 20E or DMSO was co-cultured with Escherichia coli or Bacillus subtilis , neither significantly inhibited bacterial growth (data not shown). The microflora in feeding larval midguts of silkworms have been studied extensively, and several genera of bacteria were identified that were primarily Micrococcus , Bacillus and Corynebacterium [46, 47]. In the midguts of molting larvae in this study, the cultivatable bacteria were mainly Escherichia coli and Staphylococcus aureus, even though the number was very low (data not shown).…”
Section: Resultsmentioning
confidence: 69%
“…7a; Additional file 4: Table S3). In a previous study, when the CPH45 cuticle protein was knocked-down in the silkworm, the larval midgut became abnormal after ecdysis, and the resistance of the insects to cytoplasmic polyhedrosis virus (CPV) decreased [46]. Together, these findings indicate that the insect midgut contains cuticle proteins whose expression levels change during the larva-to-larva molting stage (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Male B. mori larvae are superior to females in terms of integrated economic traits, such as resistance to cytoplasmic polyhedrosis virus, feed efficiency, silk protein synthesis efficiency, and silk quality 59 , 60 . In this study, 11 significantly differential metabolites between genders were screened to exclude the effects of genetic factor (strain) and diet (mulberry leaves and artificial diet) differences (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that even the B. mori CPH genes, in particular CPH37-40 , CPH45 as well as BMC056652_1 , BMC060920_1 and BMC057768_1, which share the highest sequence similarities with MsVMPs , may be expressed in the midgut. Indeed, a CPH -like gene ( CPH45 ) has been shown recently to be a midgut specific gene [ 22 ]. RNAi to suppress the expression of this gene delayed larval development, led to abnormal midgut morphology and resulted in decreased sex-specific tolerance to infections with cytoplasmic polyhedrosis viruses [ 22 ].…”
Section: Discussionmentioning
confidence: 99%